Healthcare in transition : understanding key ideas and tensions in contemporary health policy - Cribb, Alan (Policy Press, 2017)
Health policy thinking must change. This book explores the fundamental currents and tensions that lie behind recent trends such as shared decision-making, co-production, and personalisation. These are often discussed in relation to an epidemiological transition but this text argues that they embody a philosophical transition - a change in our conceptions of healthcare and of appropriate forms of knowledge and analysis. As clinical concerns are increasingly nested within social concerns then policy analysis must engage with the multiple philosophical tensions that are now centre stage. This focus on key underlying ideas and tensions in healthcare couldn't have come at a better time. With international relevance, the book's arguments help fuel a shift away from a 'delivery' model towards a more deliberative model of healthcare.